1999
DOI: 10.1093/emboj/18.23.6771
|View full text |Cite
|
Sign up to set email alerts
|

Host cyclophilin A mediates HIV-1 attachment to target cells via heparans

Abstract: The present study proposes a novel mode of action for cyclophilin A (CypA) in the HIV-1 life cycle. We demonstrate that CypA-deficient viruses do not replicate because they fail to attach to target cells. We show that CypA is exposed at the viral membrane and mediates HIV-1 attachment. We identify heparan as the exclusive cellular binding partner for CypA. Furthermore, CypA binds directly to heparan via a domain rich in basic residues similar to known heparinbinding motifs. This interaction between exposed Cyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
149
2
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(162 citation statements)
references
References 43 publications
10
149
2
1
Order By: Relevance
“…Our findings that HSPGs promote initial HIV-1 attachment to and entry into BMECs are in accordance with previous studies including ours, which showed that HSPGs (i.e., syndecans) greatly enhance HIV-1 adsorption onto cells that express CD4 such as macrophages (76), CD4 ϩ HeLa cells (53,75), CD4 ϩ -T-cell lines (38,62,63,73,97), or cells that lack CD4, such as primary human vein endothelial cells (15), human genital epithelial cells (94), or HeLa cells (53). This finding is also consistent with a recent study, which showed that the uptake of the basic fibroblast growth factor by the BBB is greatly enhanced by cell surface HSPGs (21).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings that HSPGs promote initial HIV-1 attachment to and entry into BMECs are in accordance with previous studies including ours, which showed that HSPGs (i.e., syndecans) greatly enhance HIV-1 adsorption onto cells that express CD4 such as macrophages (76), CD4 ϩ HeLa cells (53,75), CD4 ϩ -T-cell lines (38,62,63,73,97), or cells that lack CD4, such as primary human vein endothelial cells (15), human genital epithelial cells (94), or HeLa cells (53). This finding is also consistent with a recent study, which showed that the uptake of the basic fibroblast growth factor by the BBB is greatly enhanced by cell surface HSPGs (21).…”
Section: Discussionsupporting
confidence: 93%
“…Several receptors have been reported to facilitate HIV-1 entry into CD4-negative cells. Specifically, galactosyl ceramide (34,35,95), adhesion molecules such as ICAM-1 and LFA-1 (27,28,72), C-type lectins such as DC-SIGN, DC-SIGNR, langerin, and the mannose receptor (12,30,66,87), and proteoglycans containing chondroitin or heparan sulfate proteoglycan chains (CSPGs or HSPGs, respectively) (8,15,53,75,94) have all been shown to promote HIV-1 attachment and/or entry into cells that lack CD4. To date, there is no demonstration that these receptors are capable of mediating fusion between viral and cellular membranes.…”
mentioning
confidence: 99%
“…However, we showed that heparinase I failed to remove HS on DCs, in contrast to heparinase II and III. This enzymatic specificity is not proteoglycan-dependent because heparinase I digests HS on macrophages (22), HeLa cells (23,31), and syndecan-expressing Namalwa cells (21), suggesting that HS composition on DCs differs from that on other cells. Heparinase I cleaves HS at the level of some highly O-sulfated disaccharides, heparinase III cleaves only at hexosaminic linkages with glucuronic acid in nonsulfated or Nsulfated disaccharides, and heparinase II cleaves a variety of HS forms (32).…”
Section: Discussionmentioning
confidence: 99%
“…Supernatants (70 l) were collected and protein concentration of cell lysates measured with a Coomassie-based Bio-Rad kit. The cell lysates were then subjected to Western blotting with antibodies to CypA (26), CypB (Zymed Laboratories Inc.), CypC (Protein Tech Group, Inc.), CypD (Calbiochem), NS5A (ViroStat), and NS5B (Alexis Biochemicals). Amido Black staining of the membranes confirmed that the loading of samples had been properly normalized.…”
Section: Methodsmentioning
confidence: 99%